Emotional intelligence and job performance: the role of psychological well-being. Issue 4 (7th November 2016) - Devonish, Dwayne
Abstract : Purpose: The purpose of this paper is to test the mediating roles of two dimensions of psychological well-being (job satisfaction and work-related depression) in the relationship between emotional intelligence (EI) and task performance, individual-targeted citizenship behaviours (OCB-I) and organisation-targeted citizenship behaviours (OCB-O). Design/methodology/approach: This survey study of 262 employees in a small island territory in the Caribbean captured data on EI, psychological well-being and various dimensions of job performance. Multiple mediation hypotheses were tested using the 95 per cent bootstrapping confidence interval (CI) estimation approach. Findings: The results revealed that job satisfaction and work-related depression mediated the relationship between EI and task performance; and the relationship between EI and OCB-O, but only work-related depression mediated the relationship between EI and OCB-I. Research limitations/implications: The study utilised a cross-sectional study design and self-reported measures but still presented significant implications for existing and future theoretical models of EI and job performance. Practical implications: Organisations should seek to develop high levels of EI in their employees as a means of improving their overall psychological health and well-being and performance behaviours at work. Originality/value: The study examines multiple mediation of various psychological well-being dimensions in the EI-job performance relationship using the 95 per cent bootstrapping CI approach.